High Bandwidth Freestanding Semipolar (11–22) InGaN/GaN Light-Emitting Diodes - Zhiheng Quan; Duc V. Dinh; Silvino Presa; Brendan Roycroft; Ann Foley; Mahbub Akhter; Donagh O'Mahony; Pleun P. Maaskant; Marian Caliebe; Ferdinand Scholz; Peter J. Parbrook; Brian Corbett (IEEE Photonics Journal, 2016)
Freestanding semipolar (11–22) indium gallium nitride (InGaN) multiple-quantum-well light-emitting diodes (LEDs) emitting at 445 nm have been realized by the use of laser lift-off (LLO) of the LEDs from a 50- $μ\text{m}$ - thick GaN layer grown on a patterned (10–12) $r$ - plane sapphire substrate (PSS). The GaN grooves originating from the growth on PSS were removed by chemical mechanical polishing. The 300 $μ\text{m}$ × 300 $μ\text{m}$ LEDs showed a turn-on voltage of 3.6 V and an output power through the smooth substrate of 0.87 mW at 20 mA. The electroluminescence spectrum of LEDs before and after LLO showed a stronger emission intensity along the [11–23] InGaN/GaN direction. The polarization anisotropy is independent of the GaN grooves, with a measured value of 0.14. The bandwidth of the LEDs is in excess of 150 MHz at 20 mA, and back-to-back transmission of 300 Mbps is demonstrated, making these devices suitable for visible light communication (VLC) applications.